Interfacial Phenomena in Adhesion and Adhesive Bonding - Horiuchi, Shin; Terasaki, Nao; Miyamae, Takayuki (Springer Nature, 2024)
This open access book reviews the recent research achievements of the investigation of interfacial phenomena in polymer/polymer and polymer/metal joint interfaces with the state-of-the-art analytical techniques not previously used in the field of adhesion and bonding. Adhesion performance is determined not only by the two-dimensional interfaces but also by a three-dimensional (3D) region having different properties and structural characteristics that extends into the bulk materials. In this book, the authors also discuss in detail the bonding mechanism by characterizing such 3D regions called "interphase". The book is of great interest to researchers and engineers devoted to adhesion science and technology. Videos via app: download the SN More Media app for free, scan an image or a link with play button, and access videos directly on your smartphone or tablet.